Booth Display Model Training for Marketing of Tambak Products Produced in Tambak Oso Sidoarjo Village - D. Agustin; N. Anggriani (Future Science)
One of the marketing media that is considered quite effective is the product exhibition. By participating in the exhibition they can introduce their products and conduct market research. In the exhibition, booths or booths are needed to display their practical and attractive products. Interesting in the sense of having a beautiful shape that can support their product, practically in the sense that it can be used repeatedly and easily in terms of installation and dismantling. With the knowledge of the display booth model of processed products, the fishpond product is expected to increase sales so that it will also increase the income of the farmers in the Tambak Oso Sidoarjo village and in the future Tambak Oso Sidoarjo Village will become a Tourism Village.